Male and Female Speech in Pride and Prejudice Novel by Jane Austen and Its Implication in Teaching Speaking - Nuria Dhotul Janah; Siti Tarwiyah (Vision: Journal for Language and Foreign Language Learning, 2017)
The study of gender is essential to the study of language. It is quite clear that male and female characters are different in many aspects. They not only different in their physical aspect but also in using a language. This research aimed to uncover the differences of a linguistic feature in the speech of male and female characters based on woman’s language theory revealed by Robin Tolmach Lakoff, linguistic features which are dominantly used by male and female characters and its implication in teaching speaking. Lakoff is a linguist who began the research of the feature of woman’s language. The data of this research were taken from conversations of male and female main characters in Pride and Prejudice novel by Jane Austen. Data collection technique used was documentation which was applied two steps they are reading the novel thoroughly and enlisting all speeches uttered by the main characters of the novel. The instrument of this research was Documentation Guideline. The researcher analyzed the data by using analysis technique according to Mile and Huberman, namely data reduction, data display, and verification. This research revealed that male and female character differs in their number of using of linguistic features. Female characters are stated use more lexical hedge, avoidance of strong swear word, rising intonation on declarative, empty adjective, intensifier, emphatic stress and super polite form than male do. Female characters use those features to show their uncertainty toward things; they tend to avoid strong swear word and use more superpolite form. Therefore, female expressions are considered more polite than male. Consequently, they can avoid friction in their conversation and build effective communication across gender. This result is in line with Lakoff theory. The researcher found that the feature which is dominantly used by male and female is an intensifier. Furthermore, the implication of this research in teaching speaking especially complimenting and interrupting expression as the functional expression is the student needs to exposed expressions of complimenting and interrupting appropriately.